Percutaneous Endoscopic Gastrostomy Tubes Can Be Considered Safe in Children: A Single-Center 11-Year Retrospective Analysis - Antonia Jeličić Kadić (MDPI AG, 2021)
Background and Objectives: When the human body is disabled to naturally ingest food through the mouth, enteral or parenteral nutritional support should be started. Percutaneous gastrostomy (PEG) is a flexible feeding tube that is inserted into the stomach through the abdominal wall in patients who will need long-term enteral nutrient intake. The aim of this study is to analyze clinical characteristic of children at the time of PEG placement as well as to determine indications, complications and outcomes associated with PEG at the Department of Pediatrics of the University Hospital of Split. Materials and Methods: Retrospective analysis of the medical records of patients treated from 2010 to 2020 was performed. The following data were collected from medical records: age, gender, information about nasogastric feeding before PEG placement, indication for PEG insertion, duration of PEG, procedure-related complications and treatment outcomes. Malnutrition was determined according to the z-score range for BMI for age and sex. According to the indication for PEG placement, patients were divided into five categories: central nervous system (CNS) diseases, neuromuscular diseases, genetic disorders, metabolic diseases, and group of children with polytrauma. Results: A total of 40 patients with median age of 110 months were included in study. At the time of PEG placement, most patients had deviations in body weight and height compared to expected values for age and sex. The most common underlying diagnoses were diseases of the central nervous system. Minor complications were found in 13 (35%) of patients. One patient (2.7%) developed major complication (gastrocolic fistula) and consequently underwent reoperation. The median duration of PEG in patients with complications before the need for replacement was 27 months, and in patients without complications, 43 months. Conclusions: Negative deviations of z-score body weight, body height, and body mass index could indicate the need for possible earlier placement of PEG. PEG can be considered as a safe therapeutic option in children since PEG-related complications, mostly in minor forms, were found in a small number of patients.